Atypical Multiple Sclerosis Overlapping Features of Neuromyelitis Optica Spectrum Disorders (NMOSD) - Sepideh Paybast; Ali Emami; Nasim Rezaeimanesh; Abdorreza Naser Moghadasi (Clinical Case Reports, 2025)
ABSTRACT We aim to discuss the importance of accurately diagnosing atypical inflammatory demyelinating diseases (IDD), particularly neuromyelitis optica spectrum disorders (NMOSD), which exhibit similar pathological characteristics to multiple sclerosis (MS). An accurate diagnosis is crucial as the disease‐modifying treatments (DMTs) used for MS can be ineffective or even exacerbate NMOSD. Our case was a 20‐year‐old man who presented with acute quadriparesis and hyperreflexia. Brain and cervical MRI revealed several T2‐weighted hyperintensities in the periventricular and corticomedullary junction areas. The CSF analysis showed six oligoclonal bands restricted to the CSF, and the serum AQP4‐IgG was negative. The patient was diagnosed with an atypical relapsing and remitting MS based on the 2017 revised McDonald criteria and was treated with intravenous methylprednisolone and therapeutic plasma exchange. Eventually, his EDSS score improved from 8.5 to 3 after treatment with rituximab. Accurate diagnosis of atypical cases of IDD is not only to prevent potential harm associated with misdirected therapies but also to promptly initiate the most effective treatment. Vigilance for diagnostic red flags in MS is particularly important given its clinical and radiographic overlap with NMOSD.